Experimental studies of different quenching media on mechanical and wear behavior of Al7075/SiC/Al2O3 hybrid composites - Ravikumar, M.; Reddappa, H.N.; Suresh, R.; Sreenivasa Reddy, M. (Frattura ed integritá strutturale, 2021)
The effects of SiC-Al2O3 particle in the Al alloy on the mechanical and wear characteristics of stir-casted Composites have been reported. The Al7075 is reinforced with 2, 4, 6 and 8 wt. % of (SiC + Al2O3) to manufacture the hybrid composite. Ceramic particulates were added into Al alloy to achieve the low wear rate and improving mechanical properties. Hardening of casted specimens at 480ºC for the duration of 2 hrs and the specimens were quenched into two different quenching media (water and ice cubes). Finally, age-hardening were carried out at the temperature of 160ºC for the duration of 4 hrs and cooled at room temperature. The tensile strength, hardness and wear behaviour of MMCs are evaluated on the un-treated and heat treated composite. The tensile strength and hardness of MMCs increases by incorporating SiC-Al2O3 particulates. The wear behaviour of the MMCs containing SiC-Al2O3 particulates revealed the high wear-resistance. The heat-treatment had considerably improved the properties when compared to the un-heat treated composites. The composites with the highest tensile strength, hardness and enhanced wear resistance were found in the composites quenched in ice cubes. Worned surfaces of the composite specimens were studied by using SEM and XRD analysis